An Empirical Analysis of the Product-Process Matrix - Safizadeh, M. Hossein; Ritzman, Larry P.; Sharma, Deven; Wood, Craig (Management Science, 1996)
Process choice, a major part of operations strategy, is a key decision that links operations to business strategy. Hayes and Wheelwright, among others, argue that the emphasis given to product customization and other competitive priorities should agree with process choice. Our empirical study investigates whether firms actually link their process choice to product customization and other competitive priorities as hypothesized, and whether compatible decision patterns lead to better performance. Analysis of data collected from managers at 144 U.S. manufacturing plants shows a strong correlation between process choice, product customization, and competitive priorities. Process choice is highly related with the degree of product customization, and also with the emphasis placed on the quality and cost competitive priorities. Job shops and batch shops tend to have more product customization, higher costs, and higher quality. Some continuous flow shops use part commonality and flexible automation to achieve more customization than would otherwise be expected. Without these initiatives, customization in continuous flow shops results in weak performance.